The Psychoanalysis of Life, or Gaston Bachelard’s Reading of The Songs of Maldoror (in Polish) (Diametros, 2016)
In 1939 Gaston Bachelard published a book Lautréamont on the poem The Songs of Maldoror (Les Chants de Maldoror) by Isidore Ducasse. Bachelard’s Lautréamont was inspired by the method of psychoanalysis. The purpose of this article is to analyze Bachelard’s interpretation of the Chants, to compare his version of psychoanalysis with the versions of Freud and Jung, and to show its meaning in the historical and philosophical context.
Keywords: Gaston Bachelard; Comte de Lautréamont; Isidore Ducasse; The Songs of Maldoror; psychoanalysis; literature; French contemporary philosophy